Caracteriza????o de isolados brasileiros de Aspergillus terreus por espectrometria de massa MALDI-TOF - Motta, Dielle de Oliveira (2014)
The identification of filamentous fungiis traditionally based on morphological and biochemical criteria which are time demanding and for which results can be inaccurate. This fact motivated the evaluation of matrix-assisted laser desorption ionization ??? time of flight (MALDI-TOF) mass spectrometry for the identification of 36 brazilian isolates of Aspergillus terreus. The species is important worldwide due to its ability to produce lovastatin, a drug extremely successful in decreasing plasmatic cholesterol and consequently decreasing the risk of cardiovascular disease, main cause of death worldwide. Prior to MS analysis, the sequencing of internal transcribed spacer (ITS) allowed the identity confirmation of 94% of samples when compared GenBank database. First of all with the aim to compare the molecular biological technique with identification for MALDI-TOF was evaluated the influence of important factors in the quality of mass spectrums and then selected those more suitable to the identification of the specie. This enabled to characterize the proteic profile 30 of the 36 isolates. Nevertheless only 20% of brazilian isolates were identified as A. terreus when compared at the almost 4000 organisms of Biotyper database which may be attributed to the low representation of the specie. The results show that there are strong evidences that the technique is suitable which corroborates with this is: the similar pattern in the dendograms generated for each methodology, the ability to distinguish of the isolates comparatively higher by MALDI-TOF and the proven effectiveness of the technique evaluated by dark tests from the construction of a personal library. For these reasons the use of MALDI-TOF in the identification of isolates of A. terreus in replacing the conventional techniques is promising nevertheless requires optimizations regarding standardizing the processing of samples and inclusion of more reference spectra in the specie in database.